Utilization of Instructional Facilities and Academic Performance of Students in Public Secondary Schools in Rivers State - Ohia, Adanma Ngozi (Advances in Social Sciences Research Journal, 2019)
This studied examined the relationship between utilization of instructional facilities and the academic performance of students in public senior secondary schools in Rivers state. One research question and one hypothesis guided the study which has a correlational research design. The numerical strength of the population was 2,350 teachers in 261 senior secondary schools. Using stratified random sampling technique, the sample size was 342 respondents. To collect data, two researcher structured instruments used are “Utilization of Instructional Facilities Questionnaire (UIFQ) and Students’ Academic Performance Scale’’ (SAPS). These instruments were validated by experts and their internal consistencies were established using Cronbach Alpha method yielding reliability index of 0.79 and 0.81 respectively. The research question was answered using Pearson Product Moment Correlation (r) while the hypothesis was analysed using z-test at 0.05 level of significance. Findings of the study showed a positive relationship between effective utilization of instructional facilities and students’ academic performance. Recommendations include the need for increased utilization of provided instructional facilities in Rivers state public senior secondary schools to enhance teaching-learning process for the ultimate increased academic performance of the students.